Analyzing The Protection Of Cloud Security Against Cloud Security Risks With Secure Coding Mechanisms - Alam, Anees; Singh, Vaishali (Cuestiones de Fisioterapia, 2025)
Cloud computing is a technology that supports data and applications by using a central server and theinternet. The user can use the Internet to access the application and data from any computer. By combiningprocessing, bandwidth, and storage memory, this technology enables far more efficient computing. Onemethod that supports all IT operations is cloud computing. Rather than relying on internal performance andinfrastructure, it utilizes on-demand IT services to remove the technological barriers that organizations mustovercome in order to design information. Because organizations save their most sensitive data on the cloud,data reliability is the main problem when discussing cloud computing.